A life stage resolved habitat model for guiding seagrass restoration in coastal lagoons - Sherry Y. Zhai; Michelle Waycott; Ryan Lewis; Emma O’Loughlin; Paul L.A. Erftemeijer; Peisheng Huang; Justin D. Brookes; Claire Sims; Zhenming Zhang; Matthew R. Hipsey (Ecological Indicators)
Coastal lagoons are productive ecosystems supporting diverse biota but are susceptible to altered flow regimes and nutrient enrichment. The Coorong Lagoon in South Australia faces significant threats from reduced freshwater inputs and eutrophication, with the keystone macrophyte species, Ruppia tuberosa, generally in a state of decline. Identifying management strategies to guide their recovery has proven complicated due to the complex environmental requirements across life stages. This study aimed to develop a novel phenology-based habitat suitability model for quantifying the overall probability of reproductive success, based on salinity, water depth, light availability, temperature and filamentous algae presence. High-resolution predictions from a coupled hydrodynamic-habitat suitability model were validated against individual life stage data and reproductive outcomes (sexual and asexual) under both typical and atypical (La Niña) climatic conditions, achieving statistically significant (P < 0.05) correlation coefficients for all life stages under typical conditions. Results revealed considerable inter-annual variability in total areas suitable for reproduction between 2018 and 2022, primarily influenced by salinity and light availability during early stages (germination and sprouting) and reproductive stage. 2018 had the largest suitable areas for reproduction, while 2021 had the smallest. Under typical conditions, the central part of the lagoon was identified as a high conservation value area for R. tuberosa, offering optimal conditions for both sexual and asexual reproduction. This study highlights the importance of incorporating phenology into habitat models and demonstrates how such models can guide management decisions aiming at restoring not just the adult plant phase but also ensuring reproductive success and long-term resilience of the R. tuberosa community.